ANALISIS PEMANFAATAN SARANA DAN PRASARANA PENDIDIKAN DI TK PERTIWI KECAMATAN TEBAS - Listika Nuraini; Marmawi R,; Desni Yuniarti (Universitas Tanjungpura, 2020)
AbstractThis study aims to describe the utilization of educational facilities and infrastructure in Pertiwi Kindergarten, Tebas District. The research method used is descriptive with qualitative form of research, research data are presented in the form of words instead of numbers. Data collection techniques used in this study are direct observation techniques, communication or interview techniques, documentary study techniques, while data collection tools such as interview guides, observation alloys, and documentaries. The data source of this research is the principal and teacher of class B. The results of research on the utilization of educational facilities and infrastructure, namely, the use of learning facilities in the form of outdoor playgrounds has been utilized to the fullest, but one of the indicators of the use of facilities has not been implemented in outdoor games in education in the form of educational goal indicators . Utilization of educational facilities in the form of visual media has been maximally utilized in education, but there are still obstacles teachers in utilizing visual media in the form of number cards and picture cards. Utilization of infrastructure in the form of playgrounds has been realized for the development of children and can meet applicable guidelines.Keywords: Educational, Utilization Of Facilities And Infrastructure